1998
DOI: 10.1021/ac971107g
|View full text |Cite
|
Sign up to set email alerts
|

Confinement and Manipulation of Individual Molecules in Attoliter Volumes

Abstract: We report observation of fluorescence from individual rhodamine 6G molecules in streams of charged 1-μm-diameter water droplets. With this approach, illumination volumes comparable to diffraction-limited fluorescence microscopy techniques (≤500 aL) are achieved, resulting in similarly high contrast between single-molecule fluorescence signals and nonfluorescent background. However, since the fluorescent molecules are confined to electrically charged droplets, in situ electrodynamic manipulation (e.g., focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 24 publications
1
45
0
Order By: Relevance
“…To manipulate still ultrasmaller volumes of liquids in such diverse fields as cell biology, microfluidics, capillary chromatography, and nanolithography, one needs a better understanding of fluid behavior confined in attoliter volume. [1][2][3][4][5][6][7] Indeed, water in nanometer-sized restricted geometries, such as micelles and microemulsions, 8,9 nanometer films, 10,11 and nanoporous silica, 12 often shows different and sometimes unexpected features in comparison to bulk water. The trend of miniaturization in conventional microchip devices consisting of poly(dimethylsiloxane), silicone, and glass has thus directed growing attention to new femtoliter (fL ¼ 10 À15 L) or attoliter (aL ¼ 10 À18 L) vessels like carbon 13 and silica nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…To manipulate still ultrasmaller volumes of liquids in such diverse fields as cell biology, microfluidics, capillary chromatography, and nanolithography, one needs a better understanding of fluid behavior confined in attoliter volume. [1][2][3][4][5][6][7] Indeed, water in nanometer-sized restricted geometries, such as micelles and microemulsions, 8,9 nanometer films, 10,11 and nanoporous silica, 12 often shows different and sometimes unexpected features in comparison to bulk water. The trend of miniaturization in conventional microchip devices consisting of poly(dimethylsiloxane), silicone, and glass has thus directed growing attention to new femtoliter (fL ¼ 10 À15 L) or attoliter (aL ¼ 10 À18 L) vessels like carbon 13 and silica nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51][52][53][54][55] Secondly, the seminal work by Manz and co-workers on chip-based capillary electrophoresis [56,57] helped many concepts, such as lab-on-a-chip or micro-total analysis systems, [58][59][60][61][62][63][64] micro-flow injection analysis, [65] lab-ona-CD, [66][67][68] and microfluidic processors, [69] to emerge and find applications in analytical chemistry and biochemistry, diagnostics, [70] and research in life sciences. [71][72][73] These concepts come with various exciting flavors, such as parallelism, [74,75] fast time to result, [76][77][78][79][80] portability, [81][82][83] high sensitivity, [84] small volume of sample, [85] high-quality data, [57,86,87] heterogeneous phase reactions with large surface-to-volume ratios, [16] efficient particle/cell sorting, [88][89][90] or reactions done at liquid interphases. [...…”
Section: Introduction To Microfluidic Systemsmentioning
confidence: 99%
“…Since geometric effects play a significant role in the pattern formation, one should be able to take advantage of the powerful microfabrication technology both to explore the consequences of this observation and to provide stringent tests of theoretical models. This system may also find application as a component in a microfluidic screening chip, since it has been shown that subnanoliter vesicles have significant potential as tools for screening of biological and synthetic compounds [14][15][16].…”
mentioning
confidence: 99%